KONSTRIBUSI MOBILITAS SISWA SMAN FAVORIT TERHADAP KINERJA RUAS JALAN DI KOTA BANDUNG - Supratman Agus; Ifan Maulana; Juang Akbardin (Jurnal Transportasi, 2011)
The volume of traffic on the road sections leading to the center of the City of Bandung is influenced by the number of vehicles used by students of favorite school located in the center of Bandung. This study was carried out on the trips made by the students of the state favorite schools in Bandung and the impact of the trips on the performance of the road. The results indicate that if there were not any journey undertaken by students heading to favorite schools, the degree of saturation of road or the potential traffic congestion on the road could have been reduced.Keywords: favorite schools, traffic volume,road service level.